A procedure to correct the effects of a relative delay between the quadrature components of radar signals at base band. - Westman, A.; Grydeland, Tom; Belyey, Vasyl; La Hoz, Cesar (European Geosciences Union, 2005)
The real and imaginary parts of baseband signals are obtained from a real narrow–band signal by quadrature mixing, i.e. by mixing with cosine and sine signals at the narrow band’s selected center frequency. We address the consequences of a delay between the outputs of the quadrature mixer, which arise when digital samples of the quadrature baseband signals are not synchronised, i.e. when the real and imaginary components have been shifted by one or more samples with respect to each other. Through analytical considerations and simulations of such an error on different synthetic signals, we show how this error can be expected to afflict different measurements. In addition, we show the effect of the error on actual incoherent scatter radar data obtained by two different digital receiver systems used in parallel at the EISCAT Svalbard Radar (ESR). The analytical considerations indicate a procedure to correct the error, albeit with some limitations due to a small singular region. We demonstrate the correction procedure on actually afflicted data and compare the results to simultaneously acquired unafflicted data. We also discuss the possible data analysis strategies, including some that avoid dealing directly with the singular region mentioned above.